PENGEMBANGAN MODEL PEMBELAJARAN PERMAINAN HOCKEY CERIA DALAM PEMBELAJARAN PENJASORKES SMA NEGERI 1 BOJA TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to produce a model of learning development that aims to increase student motivation motion for SMA Negeri 1 Boja . The method of research is the development of a model refers to the development of Brog and Gall : ( 1 ) to analyze the products that will be developed from the results of field observations and literature review , ( 2 ) developing the initial product form , ( 3 ) evaluation of experts ( 4 ) revision of the initial product , ( 5 ) large -scale field trials , ( 6 ) the revision of the final product after conducting field trials large scale , ( 7 ) the end result Cheers hockey game models on N 1 Boja high school students .. From the research data , the data that the expert evaluation , expert penjas 76 % ( good ) , 84 % of learning experts ( good ) , small -scale trials of the questionnaire obtained an average percentage of 82.33 corresponding answer choices % ( good ) . As for the large -scale field trials of the questionnaire the average percentage of the corresponding answer choice 84.89 % ( excellent ) . Based on the results above , it can be concluded that the model of the game